2016
DOI: 10.1155/2016/7692387
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Photodynamic Therapy in the Treatment of Peri-Implantitis

Abstract: Introduction. The aim of this study is to demonstrate the effectiveness of addition of the antimicrobial photodynamic therapy to the conventional approach in the treatment of peri-implantitis. Materials and Methods. Forty patients were randomly assigned to test or control groups. Patients were assessed at baseline and at six (T1), twelve (T2), and twenty-four (T3) weeks recording plaque index (PlI), probing pocket depth (PPD), and bleeding on probing (BOP); control group received conventional periodontal thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…In the present study, no AE was observed in any patient of the two groups. This is in agreement with the reported safety profile of PVD . Nevertheless, once again, due to the wide choice of lasers and photosensitizers available on the market, different combinations should be explored to determine the safety profile of each one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, no AE was observed in any patient of the two groups. This is in agreement with the reported safety profile of PVD . Nevertheless, once again, due to the wide choice of lasers and photosensitizers available on the market, different combinations should be explored to determine the safety profile of each one.…”
Section: Discussionmentioning
confidence: 99%
“…PDT combined with some forms of mechanical debridement can be used for the management of peri‐implantitis. Romeo et al . indicated that PDT was a useful adjunctive therapy to mechanical debridement, but that it could not replace, for now, mechanical and surgical treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrated improvement in clinical outcomes of patients with peri-implantitis when aPDT was combined with mechanical debridement [60,80,81]. Romeo et al [82] suggested that PDT is a useful adjunct therapy but it could not replace the mechanical and surgical treatment of peri-implantitis. Similarly other studies suggest that the PDT improves the outcomes of peri-implantitis [60,83,84].…”
Section: Discussionmentioning
confidence: 99%
“…More attention has been paid to noninvasive photochemical approaches for controlling infection, such as photodynamic therapy (PDT), for treating peri-implantitis [15][16][17][18]. PDT involves three ingredients.…”
Section: Introductionmentioning
confidence: 99%